Energy Efficiency in Artisanal Brick Production in Peru: Study of the Mk3 Kiln And Its Cogeneration System - Romani Mancha, Jhoselyn Tania (2025)
The study focuses on the energy efficiency of the MK3 kiln through the cogeneration system, as a solution to reduce the use of natural resources that are currently used in the artisanal kiln to generate combustion in the production of artisanal bricks. The results in the brick firing process were obtained in the first 30 minutes, with a temperature of 410.8 °C, marking the beginning of the firing process, at 150 minutes, it reached 771.2 °C, generating efficient thermal insulation. At 240 minutes, the kiln reached 975.4 °C, evidencing the completion of the firing of the brick. The MK3 kiln stands out for its exceptional energy by using an innovative cogeneration system that is equivalent to a temperature of 486.5 °C, obtaining an energy efficiency of 50% in the continuous brick firing system, generating a positive impact on sustainable development., thus reducing fuel consumption in the brick firing process. Likewise, the result of the compression brick resistance is 60 kg/cm², exceeding the minimum resistance of 35 kg/cm², established by the masonry technical standard E0.70, indicating a better quality of the brick and a greater production in the brick industry. Finally, the results obtained in the MK3 kiln highlight the relevance of energy efficiency in the production of artisanal bricks, establishing a notable milestone in environmental sustainability, thus contributing to climate change.